The influence of polyester resin composition on fiber-matrix interphase properties - Rot, Katarina (Kovine zlitine tehnologije, 1999)
Properties of glass-fiber reinforced polyesters depend on resin and glass type, on fiber weight fraction, on processing, and on structural variables. The tensile properties of different types of E-glass-fiber chopped strand mat reinforced polyester laminates were analysed. The influence of unsaturated polyester resins composition, styrene content and type of glass-fiber on interphase properties, which dictate polyester laminate tensile strength, were determined and correlated.
Keywords: kompoziti; poliestrski laminati; poliestrske smole; steklena vlakna; natezna trdnost